Carcinoma mucoepidermóide de glândulas salivares: características clinicopatológicas e imunoexpressão de c-erbB-2 - Vanessa de Fatima Bernardes (2007)
Salivary glands tumors are rare and morphologically diversified, so, there are few papers about only one histologic type. Mucoepidermoid carcinoma (MEC) is the most common malignant neoplasm of major and minor salivary glands. The histological appearance of MEC is diversified and is correlated with the biological behavior of the tumor. Oncogene c-erbB-2 presents amplification in various neoplasms. The protein expression is observed in glandular neoplasms although the association with clinicopathological features is controversial. This study evaluated clinicopathological features of intraoral mucoepidermoid carcinoma and the association with immunohistochemical expression of c-erbB-2. The protocol was approved by the Committee of Bioethics in Research(345/05). There were 40 cases of mucoepidermoid carcinoma in Laboratory of Oral Pathology, School of Dentistry, Federal University of Minas Gerais and 32 cases were selected for the study. It was observed prevalence in female gender (78,1%), and tumors were more frequent in the age between 21 and 40 years (46,9%). The palate was the most common site affected (65,6%). Microscopically, 30 cases (93,8%) were classified as low grade of malignancy. The c-erbB-2 expression was considered negative in 22 (68,8%) cases. Chisquare test was performed using SPSS program. There were no significant differences (p > 0,05) among protein expression and gender and age of patient and site and histological grade of the lesion. In the appraised sample, c-erbB-2expression was not associated with clinicopathological features ofmucoepidermoid carcinoma of salivary glands.